2019
DOI: 10.1038/s41380-019-0439-8
|View full text |Cite|
|
Sign up to set email alerts
|

The genomic basis of mood instability: identification of 46 loci in 363,705 UK Biobank participants, genetic correlation with psychiatric disorders, and association with gene expression and function

Abstract: Genome-wide association studies (GWAS) of psychiatric phenotypes have tended to focus on categorical diagnoses, but to understand the biology of mental illness it may be more useful to study traits which cut across traditional boundaries. Here, we report the results of a GWAS of mood instability as a trait in a large population cohort (UK Biobank, n = 363,705). We also assess the clinical and biological relevance of the findings, including whether genetic associations show enrichment for nervous system pathway… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 49 publications
6
62
0
Order By: Relevance
“…Lack of power is the most likely explanation for the absence of significant results. Previous studies on other psychiatric disorders report shared genetic risk between traits and diagnoses, with polygenic risk and genetic correlations similar to what we report for OC traits and OCD case/control status [38,64,65]. The shared genetic risk between OC traits and OCD supports the hypothesis that an OCD diagnosis could represent the high extreme of OC traits that are widely distributed in the general population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lack of power is the most likely explanation for the absence of significant results. Previous studies on other psychiatric disorders report shared genetic risk between traits and diagnoses, with polygenic risk and genetic correlations similar to what we report for OC traits and OCD case/control status [38,64,65]. The shared genetic risk between OC traits and OCD supports the hypothesis that an OCD diagnosis could represent the high extreme of OC traits that are widely distributed in the general population.…”
Section: Discussionsupporting
confidence: 89%
“…Rare CNVs in PTPRD have been identified in cases with OCD [29], ADHD [34] and with brain malformations at birth [35]. SNPs in PTPRD were genome-wise significantly associated with ASD [36], restless legs syndrome [37], and self-reported mood instability [38]. Ptprd-deficient mice show learning deficits and altered long-term potentiation magnitudes in hippocampal synapses [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, large-scale whole exome (WES) or genome (WGS) sequencing studies conducted on increasingly large (and more diverse) samples are anticipated in the near future to identify many new, rare SZ risk variants. Continuously larger samples are available from national biobanks, of which the UK Biobank is a stellar example of productivity [14,15]. Environmental factors (some of which can in turn be modified by genetic phenotypes of parents and children), such as level of stress, viral infections, nutritional deficits, and family cognitive characteristics may add or subtract risk, independently, or through interaction with genetic factors to increase susceptibility risk in more complex models, some including epigenomic components.…”
Section: Introductionmentioning
confidence: 99%
“…41 A recent study reported that emotional instability showed a significant genetic overlap with bipolar disorder, unipolar depression, and anxiety. 42 Additional studies are needed to determine the biological correlates of positive assignment by bipolar screening questionnaires.…”
Section: Discussionmentioning
confidence: 99%